Evaluation of Transfusion Pyrexia: A Review of Differential Diagnosis and Management. (15th October 2012) - Arewa, Oladimeji P.
Abstract : Background/purpose . Transfusion pyrexia (fever) is an important clinical sign/symptom occurring either as an isolated event or as part of a constellation of signs and symptoms in relation to blood transfusion. It is an important cause of morbidity and may be an important sign of life-threatening complications of blood transfusion. Pyrexia is often a reason for the discontinuation of a blood transfusion episode, and adequate evaluation remains a challenge for clinicians. The decision to stop a blood transfusion episode on account of fever is often a difficult one. This paper reviews the differential diagnosis of transfusion pyrexia (TP), the pathogenesis as well as current management measures. Study selection and data source . Literature sources include medical texts, journals, dissertations, and internet-based electronic materials Results and conclusion . Adequate evaluation of pyrexia accompanying blood transfusion remains a challenge for clinicians. An algorithm to assist the clinician in the evaluation of fever occurring in a blood transfusion recipient is developed and presented. Continuous medical education is necessary for clinicians towards improved patient care in transfusion medicine.